Decreasing mortality and changing patterns of causes of death in the Swiss HIV Cohort Study1. Issue 4 (24th September 2012) - Weber, R; Ruppik, M; Rickenbach, M; Spoerri, A; Furrer, H; Battegay, M; Cavassini, M; Calmy, A; Bernasconi, E; Schmid, P; Flepp, M; Kowalska, J; et al.
<x xml:space="preserve">Abstract</x> Background Mortality among HIV‐infected persons is decreasing, and causes of death are changing. Classification of deaths is hampered because of low autopsy rates, frequent deaths outside of hospitals, and shortcomings of International Statistical Classification of Diseases and Related Health Problems (ICD‐10) coding. Methods We studied mortality among Swiss HIV Cohort Study (SHCS) participants (1988–2010) and causes of death using the Coding Causes of Death in HIV (CoDe) protocol (2005–2009). Furthermore, we linked the SHCS data to the Swiss National Cohort (SNC) cause of death registry. Results AIDS‐related mortality peaked in 1992 [11.0/100 person‐years (PY)] and decreased to 0.144/100 PY (2006); non‐AIDS‐related mortality ranged between 1.74 (1993) and 0.776/100 PY (2006); mortality of unknown cause ranged between 2.33 and 0.206/100 PY. From 2005 to 2009, 459 of 9053 participants (5.1%) died. Underlying causes of deaths were: non‐AIDS malignancies [total, 85 (19%) of 446 deceased persons with known hepatitis C virus (HCV) status; HCV‐negative persons, 59 (24%); HCV‐coinfected persons, 26 (13%)]; AIDS [73 (16%); 50 (21%); 23 (11%)]; liver failure [67 (15%); 12 (5%); 55 (27%)]; non‐AIDS infections [42 (9%); 13 (5%); 29 (14%)]; substance use [31 (7%); 9 (4%); 22 (11%)]; suicide [28 (6%); 17 (7%), 11 (6%)]; myocardial infarction [28 (6%); 24 (10%), 4 (2%)]. Characteristics of deceased persons differed in 2005 vs. 2009: median age (45 vs. 49 years, respectively); median CD4 count (257 vs. 321 cells/μL, respectively); the percentage of individuals who were antiretroviral therapy‐naïve (13 vs. 5%, respectively); the percentage of deaths that were AIDS‐related (23 vs. 9%, respectively); and the percentage of deaths from non‐AIDS‐related malignancies (13 vs. 24%, respectively). Concordance in the classification of deaths was 72% between CoDe and ICD‐10 coding in the SHCS; and 60% between the SHCS and the SNC registry. Conclusions Mortality in HIV‐positive persons decreased to 1.33/100 PY in 2010. Hepatitis B or C virus coinfections increased the risk of death. Between 2005 and 2009, 84% of deaths were non‐AIDS‐related. Causes of deaths varied according to data source and coding system.